2013
DOI: 10.1177/193229681300700319
|View full text |Cite
|
Sign up to set email alerts
|

Resource Consumption and Costs of Treatment in Patients with Type 1 Diabetes under Intensified Conventional Therapy under German Real-Life Conditions

Abstract: Abbreviations: (ATC) anatomical therapeutic chemical, (BMI) body mass index, (CUA) cost-utility analysis, (HbA1c) hemoglobin A1c, (ICT) intensified conventional therapy, (NPH) neutral protamine Hagedorn, (QALY) quality-adjusted life year, (T1DM)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Moreover, we utilized Taiwan's NHIRD, which is a data source with a nationwide representative population, for a comprehensive estimation of all economic consequences of treatments reimbursed by Taiwan's NHI for individuals with T1D. A cost analysis study of basal insulins for T1D in a real‐world setting was previously conducted using Germany's claims database, but a CEA was not performed and the cost estimates were based on only a 1‐year period. The study demonstrated a trend of lower annual costs for insulin glargine users owing to the lower costs of bolus insulin, blood glucose test strips, lancets, needles and antihypoglycaemic treatments vs NPH users.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we utilized Taiwan's NHIRD, which is a data source with a nationwide representative population, for a comprehensive estimation of all economic consequences of treatments reimbursed by Taiwan's NHI for individuals with T1D. A cost analysis study of basal insulins for T1D in a real‐world setting was previously conducted using Germany's claims database, but a CEA was not performed and the cost estimates were based on only a 1‐year period. The study demonstrated a trend of lower annual costs for insulin glargine users owing to the lower costs of bolus insulin, blood glucose test strips, lancets, needles and antihypoglycaemic treatments vs NPH users.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is plenty of evidence on this issue in the international literature [50]. For example, evidence has shown that compared with NPH, insulin analogues decreases the risk of severe hypoglycemia episodes by 38% (OR 0.62, 95% CI 0.42–0.91) [4], the risk of nocturnal hypoglycemia episodes by 46% (p = 0.04) [51], the risk of hospitalization due to the first severe hypoglycemic event by 21.7% (95% CI 9.6–32.1%,p<0.001) [52], the risk of hypoglycemic coma recurrence by 36.3% (95% CI 8.9–55.5%, p = 0.014) [52], hospitalizations by 49% [53], the incidence of macrovascular complications by 48% [54], and annual costs [55]. …”
Section: Discussionmentioning
confidence: 99%
“…This study uses a retrospective data analysis of patients with gout using health-care data extracted from electronic medical record and administrative claims databases. The following databases were used: DE—IMS Disease Analyzer™ (IMS Health, Danbury, CT, US) databases [ 33 , 34 ]; UK—Clinical Practice Research Datalink (CPRD) Hospital Episode Statistics [ 18 , 35 ]; US—IMS PharMetrics Plus database [ 36 38 ]; FR—IMS Disease Analyzer database [ 39 , 40 ]. A more detailed description of these databases can be found in Table 1 .…”
Section: Methodsmentioning
confidence: 99%